PENYULUHAN SEKSUAL DAN REPRODUKSI UNTUK MENCEGAH PERNIKAHAN DINI DI SMA 3 KOTA BENGKULU - Zelianti, Diona Dwi; Al-Fauzani, Tsabitah; Fujiarti, Resti; Yulitha, Rohmah; Akbar Pratama, M. Bintang; Yarmunida, Miti (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
The phenomenon of early marriage in Indonesia, particularly in Bengkulu City, remains a complex social issue with significant negative impacts on reproductive health, education, and socio-economic welfare. This study aims to analyze the effectiveness of sexual and reproductive health education programs as an effort to prevent early marriage among students at SMA Negeri 3 Bengkulu City, Selebar District. The research employed participatory action research using a mixed-methods approach, combining pre-test and post-test assessments, in-depth interviews, focus group discussions (FGD), and field observations. The program involved 60 eleventh-grade students as the primary participants. Results indicated a significant improvement in students’ knowledge of reproductive health, increasing from an average score of 63.5 to 87.2; a positive shift in attitudes toward continuing education, with 85.5% of students expressing a desire to complete higher education before marriage; and a comprehensive understanding of the risks of early marriage, as 91.2% of students could identify at least five negative consequences. Support from various stakeholders, including the school, religious leaders, and parents, was a critical factor in the program’s success. The study recommends integrating reproductive health education into the school curriculum and strengthening the roles of families and religious institutions in fostering a holistic understanding of marriage, aligned with Islamic legal principles and reproductive health perspectives.